Differences of energy adaptation strategies in Tupaia belangeri between Pianma and Tengchong region by metabolomics of liver: Role of warmer temperature - Feng, Jiahong; Jia, Ting; Wang, Zhengkun; Zhu, Wanlong (Frontiers in Physiology, 2022)
Global warming is becoming the future climate trend and will have a significant impact on small mammals, and they will also adapt at the physiological levels in response to climate change, among which the adaptation of energetics is the key to their survival. In order to investigate the physiological adaptation strategies in Tupaia belangeri affected by the climate change and to predict their possible fate under future global warming, we designed a metabonomic study in T. belangeri between two different places, including Pianma (PM, annual average temperature 15.01 oC) and Tengchong (TC, annual average temperature 20.32 oC), to analyze the differences of liver metabolite. Moreover, the changes of resting metabolic rate, body temperature, uncoupling protein 1content (UCP1) and other energy indicators in T. belangeri between the two places were also measured. The results showed that T. belangeri in warm areas (TC) reduced the concentrations of energy metabolites in the liver, such as pyruvic acid, fructose 6-phosphate, citric acid, malic acid, fumaric acid etc., so their energy metabolism intensity was also reduced, indicating that important energy metabolism pathway of glycolysis and tricarboxylic acid cycle (TCA) pathway reduced in T. belangeri from warmer habitat. Furthermore, brown adipose tissue (BAT) mass, UCP1 content and RMR in TC also decreased significantly, but their body temperature increased. All of the results suggested that T. belangeri adapt to the impact of warm temperature by reducing energy expenditure and increasing body temperature. In conclusion, our research had broadened our understanding of the physiological adaptation strategies to cope with climate change, and also provided a preliminary insight into the fate of T. belangeri for the future global warming climate.